An investigation on the nature of violence against women on social and online media in Zimbabwe - Sagonda, Maudy (Midlands State University, 2018)
The research is an investigation on the nature of violence against women on social and online media in Zimbabwe. A review of the causes and factors that causes violence against women on social and online media was discussed, the reason why women should not be abused and also the legal structural policies protecting women in their homes. Theories were the support bases of the thesis. Only qualitative research method was used to gather information with the use of secondary and primary sources. The researcher made use of questionnaires, interviews and documentary review in gathering data from selected population sample. The target population comprised of university students from midlands state university and Harare residents both men and women. About 95 questionnaires were distributed. The research necessarily had to use narrative language thus shona to assist in the interpretation of questions. The data gathered from the field was presented by the use of tables and pie charts. The researcher had to analyse the data she got and summarise. The data shows that women are facing violence on social and online media to a larger extent than their male counterparts; as a result the researcher had to give recommendations on what should be done to redress the nature of violence against women on social and online media in Zimbabwe.